2021
DOI: 10.1002/cncr.33573
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations and age at onset of lung adenocarcinoma

Abstract: Background To identify additional at‐risk groups for lung cancer screening, which targets persons with a long history of smoking and thereby misses younger or nonsmoking cases, the authors evaluated germline pathogenic variants (PVs) in patients with lung adenocarcinoma for an association with an accelerated onset. Methods The authors assembled a retrospective cohort (1999‐2018) of oncogenetic clinic patients with lung adenocarcinoma. Eligibility required a family history of cancer, data on smoking, and a germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Though TP53, RB1, and PIK3CA are common mutations in SCLC, the presence of these alterations was not uniform in our post-transformation genomic analyses. Therefore, it is important to consider other potential biomarkers that could be indicative of the EGFR to SCLC transformation, such as germline mutational analysis, with germline mutations in lung cancer becoming more commonly detected [ 40 ]. Any future additional therapeutic studies for EGFR TKIs should take into consideration the possibility of SCLC transformation, and perform sub-sequential histological examinations where SCLC genomic markers may not be necessarily detected by liquid biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Though TP53, RB1, and PIK3CA are common mutations in SCLC, the presence of these alterations was not uniform in our post-transformation genomic analyses. Therefore, it is important to consider other potential biomarkers that could be indicative of the EGFR to SCLC transformation, such as germline mutational analysis, with germline mutations in lung cancer becoming more commonly detected [ 40 ]. Any future additional therapeutic studies for EGFR TKIs should take into consideration the possibility of SCLC transformation, and perform sub-sequential histological examinations where SCLC genomic markers may not be necessarily detected by liquid biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies other than the two presented in the introduction [7,8] have found an unusually high prevalence of BRA1/2gl variants among LC patients. In a national Chinese multicenter retrospective study conducted in advanced stage (stage III-IV) non-small cell lung cancer (NSCLC), Hu et al [10] found a 1.03% (64 of 6220 participants) prevalence of BRCA1/2glpv which was higher than the estimated frequency in East Asians (0.2%) [11].…”
Section: Discussionmentioning
confidence: 92%
“…There was an excess of PV in cases compared to controls, resulting in an OR of 5.18 (95%CI 2.34-11-33). In addition, Reckamp et al observed that LC development was accelerated by 12 years in BRCA2glpv women carriers (95%CI, 2.5 -20.6) [8]. The main objective of the present work was to describe clinical and outcome characteristics of a series of LC patients harboring BRCA1/2gl.…”
Section: Introductionmentioning
confidence: 88%
“…Rare germline PVs in genes known to cause hereditary cancer syndromes have been associated with an earlier onset of disease in different cancers including RCC [58][59][60][61][62] , and detection of these variants with genetic testing can guide clinical management in at elevated genetic risk for cancer 63 . To further characterize the clinical impact of the rare germline PVs identified in the genes with a significantly higher burden of PVs in RCC patients, we compared the age of disease onset between the groups defined by genetic status: (1) patients carrying germline PVs in the known RCC risk genes; FH, MET, and VHL; (2) patients carrying germling PVs in CHEK2; These results, taken together with the only modest enrichment of germline PVs in CHEK2, suggests caution for considering CHEK2 as a RCC predisposition gene.…”
Section: Genesmentioning
confidence: 99%